FACTORS OF FORMATION OF PSYCHOLOGICAL DETERMINANTS IN THE PERSONAL AND PROFESSIONAL DEVELOPMENT OF PRIMARY EDUCATION TEACHERS (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article examines the factors of formation of psychological determinants in the personal and professional development of primary education teachers. The research emphasizes the role of psychological determinants as underlying mechanisms that shape teachers’ attitudes, motivation, resilience, and adaptability in the context of contemporary educational demands. The study highlights how psychological characteristics such as self-regulation, emotional intelligence, professional identity, and value orientations significantly influence the growth of teachers both as individuals and as professionals. Attention is given to the ways in which social environment, institutional culture, and pedagogical practices interact with personal qualities to form stable psychological determinants. The article also explores how these determinants contribute to coping with professional stress, maintaining motivation, and sustaining long-term commitment to teaching. By analyzing empirical studies and theoretical models, the research identifies the interplay of individual traits and external factors that shape teachers’ personal and professional growth. Special emphasis is placed on the importance of continuous professional development, reflective practices, and supportive learning communities that help teachers cultivate psychological determinants essential for their career. The study concludes that the formation of psychological determinants is a dynamic process influenced by both internal and external conditions, and recognizing these factors is crucial for the effective training and professional development of future teachers.